Coalition governments, cabinet size, and the common pool problem: Evidence from the German states - Thushyanthan Baskaran (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
The theoretical literature on common pool problems in fiscal policy suggests that government fragmentation increases public expenditures. In parliamentary regimes, the fragmentation hypothesis refers to (i) coalition governments and (ii) cabinet size. This paper explores the effect of coalition governments and cabinet size on public expenditures with panel data covering all 16 German States over the period 1975-2010. Identification is facilitated by the large within-variation in the incidence of coalition governments and the size of the cabinet in the German States. In addition, I exploit a feature of state electoral laws to construct a credible instrument for the likelihood of coalition governments.
Keywords: D78; H61; H72; 330; government fragmentation; common pool problems; coalition government; cabinet size; public expenditures